Muscular Dystrophy – Review - Bandikatla, Sarada (International Journal of Psychosocial Rehabilitation, 2020)
Muscular dystrophy is a group of genetic disorders that result in progressive loss of muscle mass and weakness. This condition results from mutation in dystrophin gene that results in synthesis of abnormal dystrophin protein leading to formation of damaged muscles. Duchenne muscular dystrophy is the most common form of Muscular Dystrophy. Most people end up in wheelchair as the muscles become weaker progressively. At present there is no treatment for this inherited diseased condition. Medications available are generally prescribed to give symptomatic relief. However, with the advancement in technology, scientists all over the world are researching for a therapy that might help people suffering from this disease by either reversing the disease or completely curing it. Of the approaches available, exon skipping, stem cell transplant are some of the areas that are being explored. This article gives a brief about the condition of muscular dystrophy, its types, causes, treatment and research area along with clinical trials that are being run for the condition.